THE RELATIONSHIP OF MOTIVATION ON THE INTEREST OF THE COMMUNITY VISITING THE DENTIST DURING THE COVID-19 PANDEMIC IN SUNGAI MIAI VILLAGE - Jailudin Muhammad Akbar; Riky Hamdani; Dewi Puspitasari (Dentino : Jurnal Kedokteran Gigi, 2023)
ABSTRACTBackground: Corona Virus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-Cov2). The COVID-19 pandemic severely limits the community environment, one of which is the limitation of dental and oral health services. The wide spread of the COVID-19 virus has caused many people to feel afraid to have their teeth checked in the midst of a pandemic, thus affecting the motivation and interest of the public to visit the dentist's practice. Objective: This study aims to determine the relationship between motivation and public interest in visiting the dentist during the COVID-19 pandemic in Sungai Miai Village. Methods: This study used an analytic observational research with a cross sectional design. The subject of this research is the Sungai Miai Village Community aged 20-55 years using a sampling technique by means of cluster random sampling totaling 113 people. Results: The results of the analysis using the Gamma test to determine the relationship between motivation and interest in visiting the dentist during the COVID-19 pandemic obtained a significant value of 0.009 (<0.05) with a correlation value of -0.52 Conclusion: There is a relationship between motivation to visit the practice dentists and interest in visiting a dentist practice with a moderate correlation strength. Keywords : Covid-19 Pandemic, Dentist Practice, Interest, Motivation, Relationship between Motivation and Interest